Visual Analysis of Activity Construction Based on Bibliometrics - Zheng , Fei; Xin, Zhang (The Global Environmental Engineers, 2022)
China has a well-developed active structure, with the continuous expansion of the scale of engineering construction and the continuous extension to the complex geological areas, especially the tectonic areas that are still active or will still be active in the future. Related projects are faced with many new challenges. The summative achievements on the problems related to active tectonics in China still need to be made available. This paper uses CNKI and WOS as data sources, and the documents related to active tectonics and geology from 2003 to 2022 are taken as objects. The scientific knowledge graph is visualized and analyzed by the bibliometrics software CiteSpace. The results show that: (1) the number of research literature on active tectonics at home and abroad is on the rise as a whole, (2) the number of articles published in the field of active tectonics in China is highly proportional to the number of earthquake disasters in China each year, and (3) the United States is in an absolute leading position in this field. It can help researchers in related fields to obtain the classical achievements of nearly 20 years quickly, and it is easy to find the bottleneck of current research. It can also expand the field of vision to find new research directions.